2021
DOI: 10.1371/journal.pone.0246998
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and contextual problems among children and adolescents in northern Chile

Abstract: Discriminatory behaviors among inter-ethnic relations in schools have long been noted and studied, but there are several correlations between discriminatory behaviors and other constructs that need further investigation. As an example, the relation between perceived discrimination and contextual problems—which include family, school and peer problems—among children and adolescents in Latin America has received little attention from previous studies. Further, the mediating role of ethnic identification and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Although Chile has specific legislation that establishes measures against discrimination (Law 20.609 of 2012, published in the Official Gazette on July 24, 2012), studies on this topic in the general population are scarce. The national literature presents mainly studies in the infant-juvenile population, where a relationship has been found between daily discrimination, substance use (Caqueo-Urízar et al, 2021) and behavioral and emotional problems (Flores et al, 2021); and in primary care users, where discrimination is associated with the presence of substance use and mental health problems (Capezza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although Chile has specific legislation that establishes measures against discrimination (Law 20.609 of 2012, published in the Official Gazette on July 24, 2012), studies on this topic in the general population are scarce. The national literature presents mainly studies in the infant-juvenile population, where a relationship has been found between daily discrimination, substance use (Caqueo-Urízar et al, 2021) and behavioral and emotional problems (Flores et al, 2021); and in primary care users, where discrimination is associated with the presence of substance use and mental health problems (Capezza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%